The Effect of Counseling with Nulliparous Women During Third Trimester on Pregnancy Outcomes - Masoumeh Delaram; Seyed Ahmad Reza Raesi Dehkordi (Majalah-i ̒ilmī pizishkī-i jundī/shapūr)
Background and Objective: Since the fear of unknown events in pregnancy and delivery increases medical interventions, this study was carried out to assess the effects of counseling nulliparous women during their third trimester on pregnancy outcomes.Subjects and Methods: This quasi-experimental study was carried out on 64 nulliparous women without abortion in their third trimester. The women, visitng Shahrekord Health Centers, were allocated randomly into counseling and non-counseling groups. In counseling group, pregnant women were counselled about the symptoms of beginning of labor, the problems could be resulted from the early admission, the benefits of normal delivery and the complications of cesarean section and familiarity with the stages of labor. The non-counseling group received the standard prenatal care. Then, maternal and neonatal outcomes were recorded. The data were analysed State the statistical method used (version 16) and P<0/05 was considered significant.Results: There was a significant difference in gestational age based on LMP (P=0.01), sonography (P=0.03), physical examination of infants (P=0.008), admission due to labor pains (P=0.04), dilatation at the time of admission (P=0.01), Taking the oxytocin (P=0.04), duration of first stage of labor (P=0.04) and mode of delivery (P=0.01) between two groups. No differences were found in weight, height, circumference and apgar score of newborns in two groups.Conclusion: Counseling with nulliparous women improved the maternal and neonatal outcomes. The findings suggest counselling nulliparous women during their third trimester of pregnancy has favorable effects on pregnacny outcome.